Sustainability of food waste biorefinery: A review on valorisation pathways, techno-economic constraints, and environmental assessment. (September 2020) - Caldeira, Carla; Vlysidis, Anestis; Fiore, Gianluca; De Laurentiis, Valeria; Vignali, Giuseppe; Sala, Serenella
Graphical abstract: Highlights: A review on valorization processes for food manufacturing waste was performed. Feedstock security, techno-economic, and environmental aspects were analyzed. Most of the valorization pathways analyzed are developed only at lab scale. Relevant aspects to ensure sustainability of biorefineries are barely considered. Abstract: The need to increase circularity of industrial systems to address limited resources availability and climate change has triggered the development of the food waste biorefinery concept. However, for the development of future sustainable industrial processes focused on the valorisation of food waste, critical aspects such as (i) the technical feasibility of the processes at industrial scale, (ii) the analysis of their techno-economic potential, including available quantities of waste, and (iii) a life cycle-based environmental assessment of benefits and burdens need to be considered. The goal of this review is to provide an overview of food waste valorisation pathways and to analyse to which extent these aspects have been considered in the literature. Although a plethora of food waste valorisation pathways exist, they are mainly developed at lab-scale. Further research is necessary to assess upscaled performance, feedstock security, and economic and environmental assessment of food waste valorisation processes.